2014
DOI: 10.1051/0004-6361/201424870
|View full text |Cite
|
Sign up to set email alerts
|

Comparing galaxy populations in compact and loose groups of galaxies

Abstract: Aims. This paper is part of a series in which we systematically compare the properties of galaxies in compact groups, loose groups, and the field. In this paper we focus our study on the age and star formation in galaxies. Methods. For galaxies in selected samples of compact groups, loose groups, and field galaxies, we compare the distributions of D n (4000) as an age indicator and the specific star formation rate as an indicator of on-going star formation. We analyse the dependence of these parameters on gala… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…6 in this paper with Fig. 6 in Sánchez et al (2015) suggests that the underlying stellar populations of H79a and H79b are old (i.e., with luminosity-weighted age 10 9.5 yrs), but prolonged star-formation activity over the last several Myr might be present (e.g., Coenda et al 2015;Sánchez et al 2015).…”
Section: The Distribution Of Ionized Gassupporting
confidence: 52%
“…6 in this paper with Fig. 6 in Sánchez et al (2015) suggests that the underlying stellar populations of H79a and H79b are old (i.e., with luminosity-weighted age 10 9.5 yrs), but prolonged star-formation activity over the last several Myr might be present (e.g., Coenda et al 2015;Sánchez et al 2015).…”
Section: The Distribution Of Ionized Gassupporting
confidence: 52%
“…These studies suggest a rapid evolution from star-forming to quiescent galaxies in compact groups. Coenda et al (2015) compared galaxies in compact groups and loose groups and found that there were two populations of late-type galaxies in compact groups, one with normal star formation rates and another with low star formation rates. If such a partition occurs preferentially along the galaxy mass/luminosity, the significant dip of HCGs could be related to the populations of late-type galaxies.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Coenda et al (2012) found a significantly larger fraction of red and early-type galaxies in CGs, as compared to loose groups, while Martínez et al (2013) established that brightest group galaxies in CGs are brighter, more massive, larger, redder, and more frequently classified as elliptical compared to their counterparts in loose groups. Coenda et al (2015) found that CGs include a late-type population with markedly reduced sSFRs compared to loose groups and field populations. The fraction of quiescent galaxies (i.e., not actively star-forming, independent of the average age of the stellar population) in CGs is higher than in the field or loose-group population (Coenda et al 2015;Lenkić et al 2016).…”
Section: Introductionmentioning
confidence: 93%
“…Coenda et al (2015) found that CGs include a late-type population with markedly reduced sSFRs compared to loose groups and field populations. The fraction of quiescent galaxies (i.e., not actively star-forming, independent of the average age of the stellar population) in CGs is higher than in the field or loose-group population (Coenda et al 2015;Lenkić et al 2016). Farhang et al (2017) compared CGs to fossil groups in the Millennium Simulation, finding that some, but not all, CGs eventually turn into fossil systems.…”
Section: Introductionmentioning
confidence: 93%